Design of a low-cost multiple output switch mode power supply - Tay, Leon Wei Sheng (Nanyang Technological University, 2023)
This project involves the development of a multiple output switch mode power supply (SMPS) intended for PC and related applications. In order for it to be cost-effective, it will be designed using the macro approach through the SPICE-based PSIM software. This will free a lot of design time leaving time to concentrate on the control circuit required for voltage regulation of the multiple outputs, required to supply power at various voltage/current levels.